Avifauna in forest fragments of the Atlantic Rainforest in the south of Espírito Santo state, Brazil - Fabio Rossano Dario (Biotemas, 2010)
This study was carried out in forest fragments located in the Atlantic Rainforest, in the town of Anchieta, south of Espírito Santo State, Brazil (located at latitude 20o40’S to 20o48’S, longitude 40o34’W to 40o42’W), along the seasons of 2008. The main objective of the study was to analyze the groups of birds that were affected by the forest fragmentation and the degree of isolation of these areas. The method used to register the avifauna specimens was the technique of observation per fixed point. Thus, the Shannon-Weaver diversity index (H’=4.18) was calculated, showing a significant abundance in the studied areas, and Equitability (E=0.81), suggesting that the number of species registered at the site represented the maximum capacity the areas were able to shelter. The Index of Point Abundance (IPA) was also calculated for each species. The IPA varied from 0.0042 (one contact) to 0.9500 (228 contacts), with a large number of species with low IPA and a few species with intermediate or high IPA. Taking into account 80 hours of observations, it was possible to register a total of 168 species of birds, distributed over a range of 45 families, 20 orders, and grouped in eight trophic guilds. Omnivores and insectivores were the most abundant, with 58 and 52 species respectively. The species most affected by the forest fragmentation were the great frugivores and understorey insectivorous birds.